Diseño de un proceso de tratamiento para remover los residuos sólidos y la carga bacteriana del río chicama para usos de riego agrícola (provincia gran chimú). - Rodríguez Castro, Gustavo Adolfo (2012)
Has designed a treatment system to move solid waste and bacterial load waters of Chicama River district of the same name in the province of Trujillo was determined that pollution of the river starts from the village of Huancay boldly refuse to its banks, as well as downloads on its way underground drains causing water pollution, altering the coloration, and the emission of foul odors, reaching the headwaters of the Annex to Sansal with 760 mg / L total solids 3:44 NMP total coliform, pH 5.74, and average 186 0805 mg / L. With these characteristics waters are diverted using channels to the agricultural area where they are used for irrigation of alfalfa fields mostly contaminated villagers, animals and plants. The sewage treatment starts at 5 m being deflected by the channels through primary treatment, consisting of the physical separation of sands, fat and remove oil making 17.67 kg / day of sand and 0.408 kg / day of fat. then the solids are filtered suspended eliminating an average of 0.55 TM / day, followed by a secondary treatment consisting of a system of sludge activated which is achieved remove 550 Kg. of suspended solids, and reduced to 65.1 mg / L. 0805, finally adding water disinfection 2.26 kg of sodium hypochlorite per day is performed, so the water must be less than total solids 200 mg / L., Total coliforms less than 100 and a pH near 7 which are suitable conditions for use of agricultural irrigation, do not try to remove insoluble solids that these are beneficial and serve as fertilizer, obtaining a water within permissible limits for irrigation use.